PENGEMBANGAN E-MODULE EKONOMI PADA MATERI UANG DAN PERBANKAN UNTUK SISWA KELAS X A SMA NEGERI 1 PANGGUL TRENGGALEK TAHUN AJARAN 2014/2015 - Nelvy Warsi Enggal Lestari; Prih Hardinto; Lisa Rokhmani (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2015)
This research was implemented because of the burnout and boredom Economics students to receive lessons because teachers only use the lecture method without any other study variation and only rely on one textbook as a source of learning. In addition, many students are reluctant to read the text book because the book is less interesting and too many posts. SMA Negeri 1 Panggul Trenggalek have been had some enough electronic facilities, but it not used optimally by the teachers in learning process. The E-Module research and development model used is ADDIE. Model with five steps, that is analysis, design, development, implementation and evaluation. In the development of this Economics E Module involves the validation of material expert and media experts from Economics professor and lecturer who are competent in the learning media. In addition, the subject of the trial in this research are all students in Tenth Grade A that about of 32 students. The result of the research and validation of material expert and media expert shows that the Econimics E-Module on Money and Banking Material is fit for use. Based on the result of pre test and post test that was gave to students before and after using the Economics E-Module indicates that E-Module is effectively used to improve the students learning outcomes.